2013
DOI: 10.1080/0267257x.2012.762184
|View full text |Cite
|
Sign up to set email alerts
|

They're gr-r-reat! Introduction to the special issue

Abstract: Sharon Ponsonby-McCabe is a lecturer in marketing communication at the University of Ulster, Northern Ireland. Her research examines axiological issues in marketing, customer co-creation, retro branding strategies, and the construction of marketing ideas.T +44 28 90368904

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One of the strongest human connections is emotional bonds and studies have found that anthropormophism and emotional connection go hand in hand (Aggarwal and McGill 2007). Until now, there has been very little research on how the gendering of a brand name impacts consumer evaluation (Brown and Ponsonby-McCabe 2013). Our results make it clear that male consumers' consumption decisions are impacted by gender bias.…”
Section: Theoretical Implicationsmentioning
confidence: 64%
“…One of the strongest human connections is emotional bonds and studies have found that anthropormophism and emotional connection go hand in hand (Aggarwal and McGill 2007). Until now, there has been very little research on how the gendering of a brand name impacts consumer evaluation (Brown and Ponsonby-McCabe 2013). Our results make it clear that male consumers' consumption decisions are impacted by gender bias.…”
Section: Theoretical Implicationsmentioning
confidence: 64%
“…The Epic Split, Dove's viral movie 'Beautiful' and the BMW movies mentioned above are examples of branded video, while the meerkats Aleksandr, Sergai and Oleg, 11 along with their vegetable counterpart, Kevin the Carrot, 12 are part of a long tradition of brand characters going back to the Pillsbury Doughboy from the 1960s, the PG Tips Chimps and Kellogg's Frosties's Tony the Tiger in the 1950s, and the Rice Crispies elves Snap, Crackle and Pop from the 1940s, deployed for their well-known ability to anthropomorphise the brand, cueing an emotional response from the consumer, and helping to make the brand easier to remember. 13 Advertising posters and billboards, often grouped together with ads on urban street furniture or bus stops as Out Of Home (OOH) advertising, and PR (Public Relations) initiatives designed to generate news coverage about brands, are both old school techniques, in contrast to influencer 14 and social media advertising which are part of the murky and hyperbolic world of digital promotion. Digital media have taken sponsorship to new places as video sharing platforms have extended audience reach for video clips of sponsored sports events to hundreds of millions, opening up opportunities for clips that have Red Bull, GoPro or Nike involved in some way.…”
Section: The Commonality Of Paratextual Advertisingmentioning
confidence: 99%
“…Indeed, there is a growing body of literature on the significance of anthropomorphism in branding. Brown and Ponsonby-McCabe (2013) suggest that people are prone to attribute human-like characteristics to all things. Marketers frequently use anthropomorphic characters – Marlboro Man, Michelin Man, Ronald McDonald, Aleksandr the Meerkat – to communicate with consumers about everything from tyres, insurance and cigarettes to fast food (Hossany et al, 2013; Patterson et al, 2013).…”
Section: Ta and Marketplace Relationshipsmentioning
confidence: 99%